Protocol for pyrotinib cardiac safety in patients with HER2-positive early or locally advanced breast cancer–The EARLY-MYO-BC study - Chai, Yezi; Jiang, Meng; Wang, Yaohui; Liu, Qiming; Lu, Qifan; Tao, Zhengyu; Wu, Qizhen; Yin, Wenjin; Lu, Jinsong; Pu, Jun (Frontiers in Cardiovascular Medicine, 2023)
Background and aim Cardiotoxicity has become the most common cause of non-cancer death among breast cancer patients. Pyrotinib, a tyrosine kinase inhibitor targeting HER2, has been successfully used to treat breast cancer patients but has also resulted in less well-understood cardiotoxicity. This prospective, controlled, open-label, observational trial was designed to characterize pyrotinib’s cardiac impacts in the neoadjuvant setting for patients with HER2-positive early or locally advanced breast cancer. Patients and methods The EARLY-MYO-BC study will prospectively enroll HER2-positive breast cancer patients who are scheduled to receive four cycles of neoadjuvant therapy with pyrotinib or pertuzumab added to trastuzumab before radical breast cancer surgery. Patients will undergo comprehensive cardiac assessment before and after neoadjuvant therapy, including laboratory measures, electrocardiography, transthoracic echocardiography, cardiopulmonary exercise testing (CPET), and cardiac magnetic resonance (CMR). To test the non-inferiority of pyrotinib plus trastuzumab therapy to pertuzumab plus trastuzumab therapy in terms of cardiac safety, the primary endpoint will be assessed by the relative change in global longitudinal strain from baseline to completion of neoadjuvant therapy by echocardiography. The secondary endpoints include myocardial diffuse fibrosis (by T1-derived extracellular volume), myocardial edema (by T2 mapping), cardiac volumetric assessment by CMR, diastolic function (by left ventricular volume, left atrial volume, E/A, and E/E’) by echocardiography, and exercise capacity by CPET. Discussion This study will comprehensively assess the impacts of pyrotinib on myocardial structural, function, and tissue characteristics, and, furthermore, will determine whether pyrotinib plus trastuzumab is a reasonable dual HER2 blockade regimen with regard to cardiac safety. Results may provide information in selecting an appropriate anti-HER2 treatment for HER2-positive breast cancer. Clinical trial registration https://clinicaltrials.gov/, identifier NCT04510532